Ecological Ethics of the Prophet: A Hadith-Based Framework for Islamic Environmental Thought - Khasani, Fahim (Journal of Modern Islamic Studies and Civilization, 2025)
The global environmental crisis shows not just ecological damage but also a deep ethical and spiritual gap between humanity and nature. This article discusses prophetic eco-ethics as an Islamic framework for caring for the environment, based on the sayings and practices (ḥadīths) of Prophet Muhammad. Using a qualitative thematic analysis approach (mawḍūʿī), the study identifies and groups selected ḥadīths that express values of ecological responsibility. These values include moderation in resource use, preservation of biodiversity, compassion toward all creatures, and keeping the environment clean as an act of faith. The findings show that the prophetic tradition provides a complete ecological ethic that combines divine accountability (tawḥīd), stewardship (khilāfah), mercy (raḥmah), and reform (iṣlāḥ) as moral duties. These values are not only spiritually important but also relevant to today’s discussions about ecology, offering a moral and spiritual way to respond to current environmental issues. The study suggests integrating prophetic eco-ethics into Islamic education, mosque-led environmental efforts, and faith-based sustainability programs.